Endobronchial sonography: feasibility and preliminary results. Issue 7 (July 1992) - Hürter, T; Hanrath, P
Abstract : Endobronchial sonography, a new ultrasound technique, has been evaluated for the assessment of normal lungs and bronchial carcinomas. The procedure was performed with ultrasound catheters, which were introduced into central and peripheral bronchi through the operating channel of fibreoptic bronchoscopes. The bronchial wall is highly echogenic and laminated. The lung parenchyma appears echo rich and patchy. Pulmonary arteries can be identified by the pulsatile changes and floating echoes within the echo free lumen. Echo poor bronchial carcinomas were detected in 69 out of 74 patients with endoscopically visible tumours and in 19 out of 26 patients with peripheral carcinomas. The correct implantation of metallic stents was facilitated by endobronchial sonography in nine patients. The sonographic examination carried no particular risk and caused little discomfort.